DISCOVERING WIRELESS NETWORKS VIA MODIFIED SCRIPTS IMPLEMENTING LINEAR ALGORITHMS FOR LINUX BASED OPERATING SYSTEMS: DISCOVERING WIRELESS NETWORKS VIA MODIFIED SCRIPTS IMPLEMENTING LINEAR ALGORITHMS FOR LINUX BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this scientific paper modified scripts, implementing linear algorithms for discovering wireless networks in Linux based operating systems are presented.